Protein adequacy is not protein optimality: a call to action in response to the new dietary guidelines for Americans - Anna Waterman; Alireza Jahan-Mihan; Zhiping Yu (Food, Nutrition and Health, 2026)
Abstract This paper argues that minimum protein adequacy should not be conflated with protein optimality in the interpretation and application of the 2025–2030 Dietary Guidelines for Americans. Although the updated guidelines provide practical, food-based protein messaging for the general public, their population-level framing may be oversimplified when translated into clinical, community, and institutional practice. This perspective distinguishes protein adequacy as the minimum intake needed to prevent deficiency in most healthy adults from protein optimization as the individualized use of protein amount, distribution, and food quality to support functional, body-composition, metabolic, and clinical outcomes. Evidence supporting higher protein intakes is reviewed with attention to the limits of nitrogen balance-derived recommendations, the public health context of obesity and chronic disease, and the population-specific nature of benefits observed in weight management, aging, illness, and physically active groups. The paper further examines how simplified public messaging may obscure important considerations, including per-meal distribution, essential amino acid quality, saturated fat exposure, energy intake, food access, and clinical status. It concludes that Registered Dietitian Nutritionists play a critical role in translating national guidance into safe, evidence-informed, and context-specific practice. A call to action is presented for the profession to strengthen education, implementation, research engagement, and policy advocacy so that protein guidance is applied with scientific nuance rather than as a one-size-fits-all prescription.